Optical temperature sensing with an Er3+, Yb3+ co-doped LaBMoO6 single crystal. Issue 7 (1st February 2023) - Li, Xinxu; Bao, Bingting; He, Xinyu; Wang, Guoqiang; Huang, Yantang; Li, Lingyun; Yu, Yan
Abstract : An Er 3+, Yb 3+ co-doped LaBMoO6 single crystal with enhanced up-conversion light emission and luminescence temperature sensing ability is grown through flux assisted spontaneous crystal growth technology. Abstract : Optical temperature sensing technology, especially the fluorescence intensity ratio (FIR) type sensor based on Er 3+, Yb 3+ co-doped up-conversion (UC) luminescent materials, presents numerous opportunities in the field of temperature detection. Various Er 3+, Yb 3+ co-doped fluorides and oxides have been explored for the application of temperature sensing. Most of these Er 3+, Yb 3+ co-doped sensing materials are phosphors, for which the high temperature phase and chemical stability is still challenging. The Er 3+, Yb 3+ co-doped oxide single crystal is a promising solution to explore temperature sensing materials with practical application ability. In this work, an Er 3+, Yb 3+ co-doped LaBMoO6 single crystal (LBMO-SC: Er 3+, Yb 3+ ) is grown through flux assisted spontaneous crystal growth technology. Compared with the Er 3+, Yb 3+ co-doped LaBMoO6 polycrystalline samples (LBMO-PC: Er 3+, Yb 3+ ), the LBMO-SC: Er 3+, Yb 3+ shows improved UC performance with enhanced light emission and prolonged luminescence lifetime. The UC performance improvement results from the more efficient energy transfer between Yb 3+ and Er 3+ . The energy transfer efficiency from Yb 3+ to Er 3+ in the LBMO-PC: Er 3+, Yb 3+ powders sintered at 1000 °C for 15 h is 7.3%, while it is 29.7% in the LBMO-SC: Er 3+, Yb 3+ . The strong UC luminescence of LBMO-SC: Er 3+, Yb 3+ extends the temperature detection range; the luminescence of 4 S3/2 → 4 I15/2 in LBMO-SC: Er 3+, Yb 3+ is still measurable even when the temperature reaches 570 K. The LBMO-SC: Er 3+, Yb 3+ has a maximum value of relative temperature sensitivity of 1.16% K −1 at 300 K. Finally, an optical fiber type temperature sensor with practical application capability is successfully fabricated by using LBMO-SC: Er 3+, Yb 3+ as the luminescence sensing medium.